Meta-analysis of meta-analyses of anterior cruciate ligament injury reduction training programs - Webster, K. E.; Hewett, T. E. (Journal of Orthopaedic Research, 2018)
Several meta-analyses have been published on the effectiveness of anterior cruciate ligament (ACL) injury prevention training programs to reduce ACL injury risk, with various degrees of risk reduction reported. The purpose of this research was to perform a systematic review and meta-analysis of overlapping meta-analyses evaluating the effectiveness of ACL injury prevention training programs so as to summarize the amount of reduction in risk for all ACL and non-contact ACL injuries into a single source, and determine if there were sex differences in the relative efficacy of ACL injury prevention training programs. Five databases (Medline, PubMed, Embase, CINAHL, and Cochrane) were searched to identify meta-analyses that evaluated the effectiveness of ACL injury prevention training programs on ACL injury risk. ACL injury data were extracted and the results from each meta-analysis were combined using a summary meta-analysis based on odds ratios (OR). Eight meta-analyses met eligibility criteria. Six of the eight only included data for female athletes. Summary meta-analysis showed an overall 50% reduction (OR?=?0.5 [0.41-0.59]; I2?=?15%) in the risk of all ACL injuries in all athletes and a 67% reduction (OR?=?0.33 [0.27-0.41]; I2?=?15%) for non-contact ACL injuries in females. This paper combines all previous meta-analyses into a single source and shows conclusive evidence that ACL injury prevention programs reduce the risk of all ACL injuries by half in all athletes and non-contact ACL injuries by two-thirds in female athletes. There is insufficient data to make conclusions as to the effectiveness of ACL injury prevention programs in male athletes.